Plastics, (bio)polymers and their apparent biogeochemical cycle: An infrared spectroscopy study on foraminifera. (15th June 2021) - Birarda, Giovanni; Buosi, Carla; Caridi, Francesca; Casu, Maria Antonietta; De Giudici, Giovanni; Di Bella, Letizia; Medas, Daniela; Meneghini, Carlo; Pierdomenico, Martina; Sabbatini, Anna; Surowka, Artur; Vaccari, Lisa
Abstract: To understand the fate of plastic in oceans and the interaction with marine organisms, we investigated the incorporation of (bio)polymers and microplastics in selected benthic foraminiferal species by applying FTIR (Fourier Transform Infrared) microscopy. This experimental methodology has been applied to cultured benthic foraminifera Rosalina globularis, and to in situ foraminifera collected in a plastic remain found buried into superficial sediment in the Mediterranean seafloor, Rosalina bradyi, Textularia bocki and Cibicidoides lobatulus . In vitro foraminifera were treated with bis-(2-ethylhexyl) phthalate (DEHP) molecule to explore its internalization in the cytoplasm. Benthic foraminifera are marine microbial eukaryotes, sediment-dwelling, commonly short-lived and with reproductive cycles which play a central role in global biogeochemical cycles of inorganic and organic compounds. Despite the recent advances and investigations into the occurrence, distribution, and abundance of plastics, including microplastics, in marine environments, there remain relevant knowledge gaps, particularly on their effects on the benthic protists. No study, to our knowledge, has documented the molecular scale effect of plastics on foraminifera. Our analyses revealed three possible ways through which plastic-related molecules and plastic debris can enter a biogeochemical cycle and may affect the ecosystems: 1) foraminifera in situ can grow on plastic remains, namely C. lobatulus, R. bradyi and T. bocki, showing signals of oxidative stress and protein aggregation in comparison with R. globularis cultured in negative control; 2) DEHP can be incorporated in the cytoplasm of calcareous foraminifera, as observed in R. globularis ; 3) microplastic debris, identified as epoxy resin, can be found in the cytoplasm and the agglutinated shell of T. bocki. We hypothesize that plastic waste and their associated additives may produce modifications related to the biomineralization process in foraminifera. This effect would be added to those induced by ocean acidification with negative consequences on the foraminiferal biogenic carbon (C) storage capacity. Graphical abstract: Image 1 Highlights: Foraminifera can use plastic debris to build agglutinated tests. Plastic debris in foraminifera can undergo oxidation. Phthalate molecule can enter the body of foraminifera. Plastic can affect foraminiferal cellules. Ocean acidification and plastic pollution can have a cumulative effect.